Karakterisasi Morfologi dan verifikasi DNA Ganoderma philippii penyebab busuk akar Acacia mangium - Desy Puspitasari; Anto Rimbawanto; Nur Hidayati (Jurnal Pemuliaan Tanaman Hutan, 2009)
The incidence of rot disese has inflicted substantial damage to some plantation of Acacia mangium in Sumatera and Kalimantan. As soil-borne pathogen, Ganoderma is commonly found in the tropic and in Indonesia the disease also couse significacant losses to rubber and soil palm plantation. To help control the disease, appropriate identification of the fungi cousing the disease and other field characteritics are critical. Morphological characteistics applied in this study has proved to be effective to identify the pathogen. The disease is predominantly caused by G. philippii. The result of morphological identicication was verified with the DNA sequence of the same fungus and confirm the accuracy of the morphological characteristics. Other fungi that attack root of Acacia mangium are G. australe and Phellinus spp.